NEUROPSYCHOLOGY CONTRIBUTIONS TO THE NEURO-ONCOLOGY MDT. (3rd October 2018) - Anderson, Stuart
Abstract: Cognitive impairment is detectable in the majority of patients presenting with primary brain tumour and is a major cause of disability, often being cited as the single greatest cause of burden to affected individuals and their carers (Locke et al. 2008). In addition, psychological reactions to diagnosis and treatment can include acute distress, anxiety and depression. Collectively, these symptoms may complicate treatment and influence quality of life (QoL). This presentation provides a rationale for the inclusion of neuropsychologists in neuro-oncology multidisciplinary teams. It summarises relevant outcomes of brain tumours and associated treatments and highlights evidence-based neuropsychological practice. This includes not only psychometric assessment but also cognitive rehabilitation and psychologically-based interventions (such as Problem Solving and Cognitive Behaviour Therapies). Learning outcomes include exposure to a specific assessment approach using the Neuropsychological Assessment Battery (NAB), components of cognitive rehabilitation, and the psychological impact of brain tumours. Reference: Locke et al (2008). Cognitive rehabilitation and problem-solving to improve quality of life of patients with primary brain tumours: A pilot study. J Support Oncol, 6, 383–391.